Resection and postoperative radiation therapy for desmoid fibromatosis of the chest wall in a young woman - Daiki Noda; Miyuki Abe; Yohei Takumi; Kentaro Anami; Michiyo Miyawaki; Hideya Takeuchi; Atsushi Osoegawa; Kenji Sugio (Surgical Case Reports, 2021)
Abstract Background Surgery is an effective treatment for desmoid fibromatosis, but it may be difficult, depending on the location or local spread of the tumor, and the decision to perform surgery must be made carefully. We herein report a case of desmoid fibromatosis of the chest wall in a young woman suspected of having invasion to the 1st, 2nd and 3rd ribs. Case presentation A 35-year-old woman had been aware of dry cough and right chest pain, so she was referred to our hospital. Chest computed tomography showed a localized pleural tumor mainly at the first rib. Magnetic resonance imaging revealed a 75 × 65 × 27-mm tumor with a smooth surface, with partial contact from the first rib to third rib and partial extension to the 1st intercostal space. The tumor showed growth in the two months after the first visit, so resection was performed. The tumor was completely resected, and adjuvant radiation therapy (50 Gy) was performed for the small margin. The pathological diagnosis was desmoid fibromatosis. The postoperative course has been uneventful, without recurrence at 14 months after surgery. Conclusions In chest wall tumors located ventral of the pulmonary apex, we suggest that a combination of the Grunenwald method and Masaoka anterior approach may be a useful option. In cases where margin is not enough, adjuvant radiation therapy should be considered.